Newspapers collection management : printed and digital challenges : proceedings of the International Newspaper Conference, Santiago de Chile, April 3-5, 2007 - Walravens, Hartmut (IFLA publications,, 2008)
Covers standards, best practice and digital developments in both historic and contemporary newspapers